ECONOMIC STUDY FOR VALUATION THE CULTURAL HERITAGE OF TEMPLES AND ARCHAEOLOGICAL SITE IN PHRA NAKHON SI AYUTTHAYA PROVINCE - Klomklaw, Kanokkarn; Pakeechai, Kanokporn; Mankong, Choklap; Supprasert, Theerasak (Journal of Social Science and Cultural, 2024)
This research article purpose to 1) study behavior in traveling to visit temples and archaeological sites, 2) evaluate the cultural heritage value of temples and archaeological sites, and 3) study guidelines for promoting preserving and restoring temples and archaeological sites in Phra Nakhon Si Ayutthaya Province. The sample group is tourists in Phra Nakhon Si Ayutthaya province 350 samples and 10 key informants. This is a mixed methods research consisting of quantitative research and qualitative research. Data were analyzed using frequency statistics, percentages, binary logistic regression analysis and semi-structured interviews. The research results found that travel behavior is learned about the information from friends/relatives, and used their own cars to travel. The main purpose of the trip is pay respect to sacred things, traveling with family, the cost is 500 - 1,000 baht, the time between activities is less than one hour, want to come back to this place again and recommend this place to others. As for cultural heritage valuation tourists are willing to pay for conservation projects, restoring temples and archaeological sites in the range of 1 - 200 baht per year. The value of willingness to pay to support the project is 194.50 baht per person per year. When considering the likelihood that tourists are willing to pay for the project, it was found that the level of net monthly income influences their willingness to pay for the project at the statistical significance level of 0.05. There is an opportunity to pay more for tourism activities 0.103 times, 0.125 times, and 0.254 times, respectively for the conservation approach. Restoration of temples and archaeological sites is conservation of archaeological sites and temples, promotion of education and learning, preservation of the environment around temples and ancient sites, promotion of cultural tourism, policy management, and creating cooperation from citizens and local agencies.